Soy-based purified ingredient diet affects mouse gut permeability and the microbiome in fragile X mice - Westmark, Cara J. (Frontiers in Molecular Neuroscience, 2025)
IntroductionGastrointestinal problems including vomiting, reflux, flatulence, diarrhea, constipation and colic are common comorbidities in fragile X syndrome. There is accumulating evidence suggesting that leaky gut syndrome causes neurological phenotypes. Although fragile X messenger ribonucleoprotein is ubiquitously expressed, there is a dearth of knowledge regarding its role outside of the brain including effects on gut dysfunction in fragile X. The aim of this study was to generate novel data on gastrointestinal barrier function and the gut microbiome in response to Fmr1 genotype, sex and diet in mice.MethodsFmr1KO male mice and littermate controls in an FVB background were maintained on two purified ingredient diets (AIN-93G with casein protein versus soy protein isolate) versus two standard chows (Teklad 2019 with wheat, corn and yeast protein versus Purina 5015 with wheat, soy, corn, yeast and whey protein sources). Gut permeability was quantified by FITC-dextran levels in blood plasma. The cecal microbiome was identified by 16S rRNA sequencing. In addition, gut permeability was tested in Fmr1KO mice in the C57BL/6 J background maintained on casein- and soy protein isolate-based AIN-93G versus Teklad 2019.ResultsKnockout of the Fmr1 gene in FVB mice did not affect gut permeability. Soy protein isolate-based AIN-93G increased gut permeability. Beta-diversity of the cecal microbiome was significantly altered as a function of the four test diets. Akkermansia_muciniphila was increased in Fmr1KO mice fed AIN-93G while unnamed species within the genus Anaerovorax and family Ruminococcaceae were increased and the order Clostridales decreased in Fmr1KO mice fed AIN-93G/soy. Fmr1KO mice in the C57BL/6 J background exhibited increased gut permeability in response to soy protein.DiscussionThese findings regarding the effects of diet on gut permeability and the microbiome have important implications for experimental design. Single-source diets are ubiquitously used to maintain laboratory animals for medical research and feed details are frequently not reported in publications. Diet/phenotype interactions could have a large impact on inter-laboratory replicability in premedical research. For infants with fragile X, early-life diet could impact the severity of disease outcomes.